De-medicalized and decentralized HIV testing: a strategy to test hard-to-reach men who have sex with men in Cameroon - Ossomba, Jean Paul Bienvenu Enama; Ngangue, Patrice; Ekani, Antoine Silvère Olongo; Kamgain, Edgar Tanguy (Frontiers in Public Health, 2023)
Conventional HIV testing performed by a health professional has shown its limitations in targeting marginalized and vulnerable populations. Indeed, men who have sex with men (MSM) due to social discrimination are often uncomfortable using this service at the health facilities level. In this perspective, new differentiated approaches have been thought through de-medicalized and decentralized HIV testing (DDHT). This HIV testing strategy enables overcoming the structural, legal, and social barriers that prevent these populations from quickly accessing HIV services. This article discusses the prerequisites and added value of implementing this strategy for MSM living in a criminalized context and its implication in decentralizing health services toward the community level.